FAKTOR-FAKTOR SOSIAL PERKEMBANGAN BAHASA ARAB - Najmah Sayuti (Jurnal Ulunnuha, 2017)
The development of a language cannot be separated from social factors existing within the users or their speakers. One factor that makes a language survive from the extinction and continue to grow is the ability of the language to accommodate the needs of the users in communicating new expressions in accordance with the user community cultural development. In the case of Arabic, social factors such as war, religion, politics and economics as well as education also play important roles in the spread and the development of the Arabic language.  They make Arabic which was just dialects of the tribes become one unified language; a language of the Bedouin became a powerful language that affects the languages around it; the Arabian Peninsula finite language became the language of the Middle East area with a significant role in the development of science and politics even today. Moreover, the revelation of Islam among the Arabs has made them and their language entities that cannot be ignored in the constellation of the international community.